Purification and densification of Ir by hydrometallurgical combined with powder metallurgical process - Jigang Li; Panchao Zhao; Wei Yi (Discover Nano)
Abstract This work shows a detailed investigation on the purification and densification of Ir target from Ir sponge by hydrometallurgy (exchange resin + extraction + chemical precipitation) combined with powder metallurgy (spray drying + pyrolysis + hot press sintering). The detailed influences of refining techniques on each impurity element and content in the Ir purified system are investigated. The controlling mechanisms of Ir particles in spray drying-pyrolysis processing are studied. The densified evolution of Ir particles during hot press sintering is revealed. After the purified treatment, high-purity Ir precursor [(NH4)2IrCl6] was achieved. The synthesized Ir particles are spherical, and the average size is about 5 μm. The purity and density of as-sintered Ir target was 99.999 wt% and 99.16%, respectively. This technological integration broke through the limitations of traditional single methods, creating a new path for the preparation of iridium powder. Moreover, atomization drying technology was applied to this research for the first time. The synergy of these technologies significantly improved the preparation efficiency and the stability of product quality. The prepared products could be used as high–reliability contact and electrode materials in the electronic information field, enhancing the performance and service life of equipment. It should be noted that the purified and densified technologies could be used to synthesize other targets of high-purity and high-density requirements.